Histone renegades: Unusual H2A histone variants in plants and animals. (15th February 2023) - Osakabe, Akihisa; Molaro, Antoine
Abstract: H2A variants are histones that carry out specialized nucleosome function during the eukaryote genome packaging. Most genes encoding H2A histone variants arose in the distant past, and have highly conserved domains and structures. Yet, novel H2A variants have continued to arise throughout the radiation of eukaryotes and disturbed the apparent tranquility of nucleosomes. These species-specific H2A variants contributed to the functional diversification of nucleosomes through changes in both their structure and expression patterns. In this short review, we discuss the evolutionary trajectories of these histone renegades in plants and animal genomes.